Enhanced thermoelectric performance in Ca-substituted Sr3SnO. (December 2018) - Haque, Enamul; Hossain, M. Anwar
Abstract: First-principles calculations were performed to study the electronic and thermoelectric transport properties of Ca-substituted Sr3 SnO (Sr3− x Ca x SnO, 3 ≥ x ≥ 0). The effects of Ca substitution on the bandgap are studied, and detailed mechanisms are proposed to explain the results obtained. We found that an increase of the hole concentration reduces the effective mass and the Seebeck coefficient of Ca-substituted Sr3 SnO. The optimum hole concentration was obtained for Sr2 CaSnO, and the corresponding maximum Seebeck coefficient of 219 μV/K was obtained at 500 K. The electrical conductivity of Sr3 SnO and its alloys has a semiconducting nature, which contradicts experimental results for Ca3 SnO. We found that Ca-deficient Ca3 SnO exhibits metallic conductivity, and this removes the contradiction with our results. The lattice thermal conductivities ( κ l ) of Sr3 SnO and Ca3 SnO were calculated by use of both the Perdew-Burke-Ernzerhof functional and the GW functional. The total thermal conductivity for Sr3 SnO and Ca3 SnO at 300 K is 3.03 and 2.06 W/(m K), respectively. The figure of merit ( ZT ) for Sr2 CaSnO at 500 K is 0.6, making it promising for thermoelectric applications. Highlights: The effects of Ca substitution on the bandgap and detailed mechanisms are proposed to explain the results obtained. The electrical conductivity of Sr3 SnO and its alloys has a semiconducting nature. A large Seebeck coefficient for Sr2 CaSnO of 219 μV/K was obtained at 500 K. The thermoelectric figure of merit (ZT) for Sr2 CaSnO at 500 K is 0.6, making it promising for thermoelectric applications.